Metarepresentations of Supernatural Belief and the Effect of Context on Cognition - Schofield, Malcolm; Sheffield, David; Baker, Ian (Journal of Scientific Exploration, 2022)
This study aimed to see if context in the form of priming can alter a participants thinking style based on their level of implicit association with either a religious or paranormal belief. This was based on the theory of alief, when a person’s explicit belief and behaviour are mismatched. This was also linked to dual process theory, with alief being analogous to type one thinking styles (fast and automatic). One hundred and seventy-two participants were recruited from the University of Derby and social media. Implicit association was measured using a modified Brief Implicit Association Test that looked at paranormal and religious belief. Explicit supernatural belief, cognitive reflection, metacognition, and confidence were also measured. A hierarchical multiple regression revealed that a lower belief in the supernatural (apart from psychokinesis), a religious prime and high confidence predicted reflective thinking. Common paranormal perceptions, religious prime and confidence were significant predictors in the model. It was concluded that the prime worked on a moral level and influenced someone with an already open mind to different beliefs to be more analytical, positive, and confident. This study does not support the theory of alief, however, it indicates certain beliefs are susceptible to a certain prime, and that a person can be influenced to be more analytical.